The reserpine-treated cat - Withrington, P. (1961)
In cats, 24 hr after the administration of 1 mg/kg of reserpine, it was found that (a) the heart is in failure; (b) the sensitivity of the peripheral vessels to adrenaline, noradrenaline and isoprenaline, administered intravenously or close-arterially, is decreased; (c) any blood pressure changes are, as a rule, secondary to changes in heart contraction; and (d) the peripheral blood flow passively follows the blood pressure changes. Furthermore, any improvement of the circulation at this stage was found to be almost exclusively the result of an amelioration in the force of cardiac contraction.